2008
DOI: 10.1162/neco.2008.05-07-516
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Synchrony of Chaos in a Pulse-Coupled Neural Network with Both Chemical and Electrical Synapses Among Inhibitory Neurons

Abstract: The synchronous firing of neurons in a pulse coupled neural network composed of excitatory and inhibitory neurons is analyzed. The neurons are connected by both chemical synapses and electrical synapses among the inhibitory neurons. By introducing electrical synapses, periodically synchronized firing as well as chaotically synchronized firing is widely observed. Moreover, we find stochastic synchrony where the ensemble-averaged dynamics shows synchronization in the network but each neuron has a low firing rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…The parameters are set as g EE = g II ≡ g int and g EI = g IE ≡ g ext for simplicity. Kanamaru & Aihara (2008) analyzed the dependence of synchronization only on g EE , g II , g EI , or g IE in the global network that corresponds to our model with p = 1 and found that the synchronous firing exists only in some range of g EE , g II , g EI , and g IE . Moreover, the time constants of the internal dynamics and the synaptic transmission are set to τ E = 1, τ I = 0.5, κ E = 1, and κ I = 5.…”
Section: The Sets Of Indices For Connections a (Ij)mentioning
confidence: 97%
See 4 more Smart Citations
“…The parameters are set as g EE = g II ≡ g int and g EI = g IE ≡ g ext for simplicity. Kanamaru & Aihara (2008) analyzed the dependence of synchronization only on g EE , g II , g EI , or g IE in the global network that corresponds to our model with p = 1 and found that the synchronous firing exists only in some range of g EE , g II , g EI , and g IE . Moreover, the time constants of the internal dynamics and the synaptic transmission are set to τ E = 1, τ I = 0.5, κ E = 1, and κ I = 5.…”
Section: The Sets Of Indices For Connections a (Ij)mentioning
confidence: 97%
“…where X = E or I, and δ ij is Kronecker's delta (Ermentrout, 1996;Izhikevich, 1999;Kanamaru & Aihara, 2008). Although the number of excitatory neurons in the cortex is much larger than that of inhibitory neurons, we set both numbers identical for simplicity.…”
Section: Network Of Excitatory and Inhibitory Neuronsmentioning
confidence: 99%
See 3 more Smart Citations